Prediction of acute myeloid leukaemia risk in healthy individuals - Abelson, Sagi; Kaaks, Rudolf; Krämer, Alwin (Nature, 2018)
Individuals who are at high risk of developing acute myeloid leukaemia can be identified years before diagnosis using genetic information from blood samples.
Gesehen am 03.04.2019